The usage of songs in the Arabic textbook and its effect on vocabulary recall: a case study at Sekolah Kebangsaan Batu Muda - Siregar, Nurhalimah; Mamat , Arifin (2015)
Song become an inspirable part of human being and most of students like to sing. Song is universal as well as language. Thus, teachers believe that song can be a pedagogical tool in teaching language. The aims of the present study is to explore the students’ perceptions towards using songs in learning Arabic and to investigate the effect of using song in Arabic textbook on vocabulary recall. Students’ perceptions towards using songs will be measured through a survey. Students’ vocabulary recall will be measured also through pre-test and post-test.